The Effect of Income and Job Type on Students’ Self-Efficacy and Achievement of Migrant Workers in Taiwan - Romi Aswandi Sinaga; Nopriani; Yi-Syun Chen (International Journal of Islamic and Social Sciences (ISOS), 2021)
The Indonesian government provides opportunities for migrant workers to continue their higher education. Through the distance learning program, migrant workers can study to develop their potential in the academic field in addition to working as foreign exchange heroes. This study investigated the current status of students’ self-efficacy and achievement of migrant workers in Taiwan and the effect of income and job type on students’ self-efficacy and achievement. 100 migrant workers in Taiwan were surveyed. The collected data were analyzed with descriptive analysis, t-Test, and one way ANOVA with Scheffe Method. To understand migrant workers with specific conditions affected by their job type, in-depth interviews were done. Findings revealed current status of students’ self-efficacy of migrant workers in Taiwan is slightly low and their achievement is moderately high. Income affects the students’ self-efficacy and achievement of migrant workers while job type affects their achievement. The self-ability to stabilize physical and emotional condition is required to improve students’ self-efficacy. Moreover, the social interaction among students, teachers, and peers is required to improve their achievement.